Pendampingan Kepada Masyarakat Tentang Manajemen Pengelolaan Gambut (Histosol: Level Hemic) Desa Keub Kecamatan Arongan Lambalek Kabupaten Aceh Barat Provinsi Aceh - Putra, Iwandikasyah; Abubakar, Yusya; Baihaqi, Akhmad; Anhar, Ashabul; Bagio; Fazlina, Yulia Dewi; Irawan, Jekki; Jalil, Muhammad (Medan Resource Center, 2022)
This assistance is expected to provide additional information about peat soil management to the people of Keub Village, Arongan Lambalek District, West Aceh Regency, Aceh Province. Farmers can independently manage any problems that arise on peat soils, so they are able to take the right steps in current and future management efforts so that the land can produce optimally. Its management includes physical (mechanical), chemical, and biological aspects. Utilization of peat based on improving the community's economy and preserving the ecology of peat requires careful and measured preparation, including; the construction of integrated canal blocks by carrying out control and evaluation through strengthening institutional capacity including communities around peat (practitioners) and academics in a holistic manner in a definitive manner, with the hope that the use of peatlands will not have a negative impact on the current and future environment.